Poder financiero y arrendadores de rentas reales en Castilla a principios de la Edad Moderna - Alonso García, David (Cuadernos de Historia Moderna, 2006)
Tax farm was an usual and constant activity for a remarkable number of financiers during the first decades of XVIth Century. This work will try offering some characteristics about tax farmer and familiar or political groups that they protected to financiers. Moreover, this article will set out some elements of financial system of Hispanic Monarchy. The work has been achieved according to New Fiscal History (Tracy), M. Vester’s methodological precisions and current analysis of merchants communities.
Keywords: Catholics Kings; Charles V; Tax farmers; Fiscal system; Financial power